Sexual Attitudes, Religious Commitment, and Sexual Risk Behaviours among College-Aged Women. Issue 8 (17th November 2021) - Armstrong, Joslyn; Thorpe, Shemeka; Williams, Denise
ABSTRACT: Sexual double standards tend to marginalize women and restrict their sexual expression in comparison to men. Sexual attitudes can heavily influence women's propensity to engage in sexual risk behaviours. One's sexual attitudes, whether more conservative or liberal have been shown to influence differing experiences of power and assertiveness in sexual relationships. Religiosity is often linked to an individual's sexual decision-making and practices. Thus, the purpose of this study was to examine if sexual attitudes meditated the relationship between women's religious commitment and their sexual risk behaviours while in college. The study consisted of 155 college-aged women (ages 18–25) who completed an online survey. The results suggested that religious commitment was significantly related to sexual risk behaviours. Additionally, sexual attitudes did not mediate the relationship between religious commitment and sexual risk behaviours. These findings provide researchers with relevant information about women's sexual attitudes and their corresponding behaviours. This study adds to the literature by focusing on the relationship between college-aged women's sexual practices and their religiosity.